Placing Another Piece of the Tethyan Puzzle: The First Paleozoic Paleomagnetic Data From the South Qiangtang Block and Its Paleogeographic Implications. Issue 10 (17th October 2022) - Wei, Bitian; Cheng, Xin; Domeier, Mathew; Jiang, Nan; Wu, Yiying; Zhang, Weijie; Wu, Ke; Wang, Baofeng; Xu, Pengxiang; Xing, Longyun; Zhang, Dongmeng; Li, Teng; et al.
Abstract: The origin and drift history of the South Qiangtang block (SQB) is critical to understanding the internal dimensions and kinematics of the late Paleozoic to early Mesozoic Tethyan realm and the subsequent evolution of the Qinghai‐Tibet Plateau, but so far no paleomagnetic data constrain the SQB in Paleozoic time. Here we present a paleomagnetic study of the middle Permian volcanic and sedimentary rocks from the SQB. Well‐defined high‐temperature components of magnetization were isolated from 6 sites of tuffaceous sandstone and 9 sites of basalt, but their directional populations are distinct. On the basis of a conglomerate test and comparisons with younger paleomagnetic data, we argue the basalts preserve a primary magnetization, whereas the sandstones may have been remagnetized during the Triassic. The magnetic directions from the basalt indicate that the SQB was located at a latitude of 22.3 ± 5.8°S during the middle Permian. Together with existing paleomagnetic data from other Tethyan continental blocks, this new constraint reveals that during the middle Permian the Neo‐Tethys Ocean spanned ∼10–20° of latitude and the Paleo‐Tethys Ocean spanned ∼50°, but also that the latter was a composite ocean system which included at least two important branches. In further considering the geological records of the SQB, we propose the block rifted from the northern margin of Gondwana during opening of the Neo‐Tethys in early Permian time, and then drifted rapidly northward until ultimately colliding with the North Qiangtang block and the southern margin of Laurasia during final closure of the Paleo‐Tethys in the Triassic. Plain Language Summary: The formation of the Qinghai‐Tibet Plateau involved the opening and closing of multiple oceans (the 'Tethyan' oceans) and the rifting, drifting and collision of multiple continental blocks, but quantitative paleogeographic constraints on the motions of these tectonic 'puzzle pieces' are scarce. Here we present paleomagnetic data from one of the central pieces of this puzzle—the South Qiangtang block—which allow us to determine that it was located at a latitude of ∼22°S in middle Permian time, 265 million years ago. This paleolatitude constraint further allows us to estimate the width of the Tethyan oceans on either side of the South Qiangtang block in the middle Permian, providing a first‐order snapshot of the evolving paleogeographic puzzle that gave rise to the Qinghai‐Tibet Plateau. Key Points: The South Qiangtang block was located at ∼22°S in the middle Permian The width of the Paleo‐Tethys exceeded 5, 500 km in the middle Permian, when the width of the Neo‐Tethys was ∼1, 000–2, 000 km The South Qiangtang block drifted rapidly northward with the Cimmerian blocks in early Permian to Late Triassic time